Feedback, rewards, and mental health for improved job performance of Oaks Residences Homeowners Association staff - Rocamora, Josef Paolo B. (Animo Repository, 2022)
After using the first, second, and third person inquiries, it was found by the collaborators that the overall purpose of the action research is for the ORHOAI security guards to have a simulation of performance appraisal, rewards system, and a mental health assessment. Going through a simulation of a written formal performance appraisal made the security guards know the status of their performance and gave them a chance to share their insights and suggestions to their supervisor and the organization; a recognition system inspired them to work harder - both of these are included in the first cycle. Next, they underwent a simulation of a regular mental health assessment, which is covered by the second cycle. After every simulation, they answered a post-survey to determine their feelings and thoughts experiencing the interventions. It was found eventually that the security guards, indeed, became more motivated as they felt good being trusted and appreciated, knowing that something is being done for their well-being. They learned as they heard their supervisor’s observations and became more open when their feedback was asked. Being recognized is something that they happily welcome as well. And last, they understood that mental health is important to improve their job performance and to simply feel better emotionally while working.